A multi-objective robust supply chain design considering reliability - Gholami, Faezeh; Paydar, Mohammad Mahdi; Hajiaghaei-Keshteli, Mostafa; Cheraghalipour, Armin (Journal of industrial and production engineering, 2019)
This paper designed a four-echelon supply chain network consist of suppliers, manufacturers, distributors and customers. Here, the allocation of raw materials and products is subject to random disruptions based on weather conditions, natural events, and ownership changes. This is an unprecedented research to simultaneously consider the parameters uncertainty and reliability of the components in a dynamic chain with multiple products. The model is a multi-objective mixed integer linear programming into which the uncertainty is incorporated by using the robust optimization. The model seeks to minimize the network's costs while the both manufacturer and customer satisfaction are maximized. To solve the model, three multi-objective decision-making methods are investigated and the best method is selected according to its performance in several examples. Also, suppliers and distributors with the highest reliability are obtained which, it enables managers to make the proper decision on both strategic and operational levels of their firms' policies.